THE USE OF STYLISTIC DEVICES IN THE CREATION OF LITERARY IMAGES IN S. MAUGHAM’S NOVEL “THE MOON AND SIXPENCE” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The present article analyses the stylistic devices and expressive means which are used in the creation of literary images in S. Maugham’s novel “The Moon and Six Pence”.